Coefficients of inbreeding and relationship among pedigree Jersey bulls used in artificial breeding or in natural mating in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the Victoria University of Wellington, Massey College - Hamilton, C O (Massey University, 1962)
Since 1950, when the New Zealand Dairy Board assumed responsibility for the commercial development of Artificial Breeding, there has been a tremendous increase in Artificial Breeding usage. Whereas in 1950,0.2% of the total cow population was artificially inseminated, the corresponding figure for 1960 was 26%. In any Artificial Breeding scheme there are dangers of inbreeding through the use of a limited number of sires, and if the young sires selected for the scheme are largely the sons of the best sires already in the scheme, then the dangers of inbreeding are increased. Inbreeding to high levels is undesirable because it generally reduces the mean level of all characters closely connected with fitness in animals and leads in consequence to loss of general vigour and fertility. Since most characters of economic value in demestic animals are aspects of vigour or fertility, inbreeding is generally deleterious. The genetic basis of this inbreeding degeneration is not completely clear. Another harmful effect of inbreeding is the possibility that it may fix undesirable genes in the homozygous state.
Keywords: Jersey cattle; Inbreeding; Breeding; Selection indexes; New Zealand